No Gender Difference in Willingness to Compete When Competing against Self - Apicella, Coren L.; Demiral, Elif E.; Mollerstrom, Johanna (American Economic Review, 2017)
We report on two experiments investigating whether there is a gender difference in the willingness to compete against oneself (self-competition), similar to what is found when competing against others (other-competition). In one laboratory and one online market experiment, involving a total of 1,200 participants, we replicate the gender-gap in willingness to other-compete but find no evidence of a gender difference in the willingness to self-compete. We explore the roles of risk and confidence and suggest that these factors can account for the different findings. Finally, we document that self-competition does no worse than other-competition in terms of performance boosting.